Impacts of Sea Surface Temperature and Atmospheric Teleconnection Patterns in the Northern Mid-Latitudes on Winter Extremely Cold Events in North China - Liping Li; Wenjie Ni; Yige Li; Dong Guo; Hui Gao (Advances in Meteorology)
The frequency distribution of winter extreme cold events (ECEs) in North China and the influences of mid-latitude sea surface temperature anomalies (SSTAs) in the Northern Hemisphere are studied. The results show that (1) the frequency of single station ECEs (SSECEs) in winter increases from southeast to northwest, with a decrease before 2008 and then a significant increase. This trend abrupt change occurs in late winter. (2) When the SST in the North Pacific shows an “El-Niño-like” anomaly in winter, it triggers the negative Arctic Oscillation (−AO), positive Pacific North America (+PNA), and positive Eurasia Pacific (+EUP) atmospheric teleconnection patterns in the mid-lower troposphere. As a result, the ridge to south of Lake Baikal becomes stronger. Meanwhile, SST in the North Atlantic shows a “reversed C” negative anomaly with North Atlantic Oscillation (+NAO), (+PNA)-like and (+EUP)-like patterns, and the ridge to southwest of Lake Baikal becomes stronger. Furthermore, both cause the Siberian High to become weaker in the north and stronger in the south. With the weaker East Asia subtropical jet and stronger East Asia winter monsoon, these factors lead to a significant increase of SSECE frequency in North China. (3) When the SSTA shows an “El Niño-like” developing pattern from summer to autumn in the North Pacific, the winter SSECE frequency will be higher. (4) The purported mechanism between the mid-latitude SSTA and the winter SSECE frequency in North China is the following: the SSTA in the North Pacific in summer and autumn excites atmospheric teleconnection wave trains, and the Atlantic stores these anomaly signals. In winter, the interaction between the SSTAs in the North Pacific and the North Atlantic enhances the Eurasian teleconnection wave train. With the upstream fluctuation energy dispersing downstream, the wave train centers move eastward with the season, resulting in an increase in the frequency of the SSECEs.